RHYTIDECTOMY AND ITS MEDICO-LEGAL IMPLICATIONS - Sabari. C H (International Journal of Research -GRANTHAALAYAH, 2025)
Rhytidectomy, or facelift surgery, is one of the most common cosmetic surgical procedures performed to reverse the effects of ageing by tightening the skin and underlying tissues of the face. The central aim of the present study is to examine rhytidectomy from clinical and medico-legal perspectives, in the context of India. This research is doctrinal, employing qualitative assessments of medical literature, legal statutes and cases to analyse legal duties and patient protection. A detailed history of the facelift is provided, as well as information on types of procedures, appropriate patient selection, preoperative protocol, and postoperative care. It also concerns itself with medico-legal matters like patient consent, negligence, and remedies for botched surgeries. The findings highlight a disconnect between surgical procedure and legal enforcement within the Indian context and the need for defined guidelines as well as accountability. This study finds that although there are many aesthetic benefits to rhytidectomy, strong legal protections and professional standards are necessary to ensure the safety and rights of patients undergoing aesthetic surgery.